Understanding the burden and influencing factors in family caregivers’ medication assistance for patients with dementia: a survey study - Mitsuko Onda; Maaya Inoue; Koki Zouchi; Masaki Shoji; Hatsuyo Maeda (BMC Geriatrics)
Abstract Background This study aimed to elucidate the sense of burden and the factors that affect medication assistance among family caregivers who provide long-term care to elderly patients with dementia. Methods Survey method: A sample size of 96 was predetermined, and a web-based survey was conducted to caregivers who met the qualifying criteria. The survey encompassed following components: (1) assessment of burden, (2) determination of difficulty during medication assistance, (3) evaluation of comprehension of medication purposes, (4) evaluation of caregiver’s ability to recall administration method, (5) measurement of satisfaction with current medication, (6) examination of harmony between medication and lifestyle habits, (7) cohabitation status with the patient, (8) quantification of oral medications, (9) determination of medication doses (doses) per day, and (10) estimation of time spent on medication assistance. The respondents were categorized into “high burden” and “low burden” groups, and the distribution of responses for items (2) to (7) was compared between these groups using a chi-square test. Mean responses for items (8) to (10) were compared between the groups using a Student’s -t test. Furthermore, multivariate analysis was performed using burden as the target variable, and significant differences identified between the groups using chi-square and Student’s t-tests as explanatory variables. The significance level was established at 5%. Results The study comprised 100 respondents, 90% of whom offered medication assistance. Among the caregivers, 38.9% reported experiencing burden, 56.7% faced challenges with medication assistance, and 36.6% faced medication refusal. Additionally, 15.5% of participants experienced disharmony between their medication and lifestyle. The multivariate analysis results highlighted associations between burden and factors such as the presence/absence of difficulty in medication assistance, number of doses per day, medication refusal, and level of harmony between medication and lifestyle. Conclusion The burden was influenced by various factors indicating “difficulty.” The study highlighted the importance of simplifying medication usage by reducing the number of doses, addressing medication refusal through third-party intervention, and customizing assistance to individual needs based on the psychological conditions of patients and caregivers. These approaches aim to alleviate disharmony between medication and lifestyle.